Implentasi Simkah Dalam Administrasi Perkawinan Di Kua Gununganyar Surabaya - Muhammad In'am Aufa; Nur Sabilatul Hidayah; Vina Rochmatul Ummah; Mas Mir'atul Mafaza Mutiara (TARUNALAW Journal of Law and Syariah, 2026)
Digitalization is the transformation of data from physical form into digital format through the use of information technology. This development has encouraged the government to improve public services, particularly in the field of marriage administration, through the introduction of an innovation known as the Marriage Management Information System (SIMKAH). This study aims to analyze the implementation of SIMKAH at the Office of Religious Affairs (KUA) in Gunung Anyar District, Surabaya City. This research employs a qualitative approach, with data collection methods consisting of observation and documentation. The implementation of SIMKAH at KUA Gunung Anyar is analyzed using Indrajit’s theory of e-government success, which includes support, capacity, and value. The findings of this study indicate that the presence of SIMKAH has improved the quality of public services at KUA Gunung Anyar. Specifically, it has enhanced the effectiveness of marriage administration management, such as the accuracy and legalization of prospective bride and groom data, as well as the prevention of data falsification. Moreover, SIMKAH ensures data security, facilitates data accessibility, and supports staff performance in enforcing legal regulations related to marriage. This includes improving the effectiveness and efficiency of service time, accelerating service delivery, and increasing public satisfaction. However, the implementation of SIMKAH still requires further improvement due to several challenges, including the lack of public socialization regarding SIMKAH services, insufficient IT staff to address technical issues, and frequent instability of the central server or network.